Ion irradiation-induced interface mixing and the charge trap profiles investigated by in situ electrical measurements in Pt/Al₂O₃/β-Ga₂O₃MOSCAPs - Manikanthababu, N. (2023)
In situ I - V and C-V measurements were performed during the 120 MeV Au9+ ion irradiation on the Pt/Al2O3/β-Ga2O3, metal-oxide-semiconductor capacitors (MOSCAPs), to comprehend the swift heavy ion (SHI)-induced effects at the interface and in the device performance. At a maximum fluence of 2× 1012 ions/cm2, the I-V data showed a rise in the reverse leakage current by four orders of magnitude compared to the pristine device. The trap level (below the conduction band of Al2O3) from Poole-Frenkel emission exhibits a variation from ∼ 1.1 to 0.91 eV. The conduction band offset (φB) of Al2O3/β-Ga2O3 changes from 1.48 to 1.25 eV as estimated under the Fowler-Nordheim tunneling mechanism. In situ C-V measurements show a significant shift in the flat band voltages and increased oxide in the border and interface due to charge trapping. The X-ray photoelectron spectroscopy (XPS) measurements of Al 2p and O 1s core levels revealed the pre-existing oxygen defects in Al2O3, which increase with fluence. The deconvoluted peaks of Al 2p at 74.6 eV designated to Al-sub oxide and the O 1s peak variation in the FWHM signifies the increase in the O defects. Cross-sectional transmission electron microscopy (XTEM) measurements on the irradiated device (at 2× 1012 ions/cm2) revealed a modulated interface of Al2O3/β-Ga2O3 and the formation of an interlayer of ~4 nm AlxGayOz. The scanning transmission electron microscope (STEM)-based high-angle annular dark-field imaging (HAADF) energy-dispersive X-ray spectroscopy (EDS) mapping revelation and the depth profiles of XPS data confirm the formation of an AlxGayOz interlayer.